Design and develoment of high performance resonant type inverter for rooftop grid connector photovoltaic application - Salam, Zainal (Universiti Teknologi Malaysia, 2004)
This thesis proposes a bidirectional high-frequency link inverter using high-frequency transformer, for grid-connected application. The proposed topology has high efficiency, light weight and low cost. In contrast with work carry out by previous researches, the power switches count is reduced, for center-tapped transformer is used. Therefore, the efficiency of the inverter is increased. As far as PWM technique is concerned, digital approach has been applied. A mathematical equation was derived to calculate the pulse width, and switching scheme for the gate signals was proposed. Furthermore a simple dead time compensation based on pulse width increment was fully implemented. As a result, output voltage distortion was reduced. The proposed topology was verified using computer simulation to study it strength and weaknesses. A 1kW prototype was implemented based on a 16-bit microcontroller. Laboratory experiments are carried out to determine the system performance and the result are very encouraging. The inverter has a maximum efficiency of 90% and low Total Harmonic Distortion (THD), which is less than 1%.